UTILIZATION OF VIRTUAL REALITY TO REDUCE ANXIETY IN ODONTECTOMY: A SCOPING REVIEW - Oktora, Saptiadi; Yusuf, Harmas Yazid; Riyanti, Eriska; Hariri, Firdaus (Journal of Posthumanism, 2025)
Odontectomy, or wisdom tooth removal, is a common oral surgery that can lead to significant anxiety, affecting patient outcomes and experiences. Virtual reality (VR) has emerged as a potential noninvasive tool for managing anxiety in medical and dental settings. This scoping review explores the effectiveness of VR in reducing anxiety during odontectomy. Following the PRISMA-ScR guidelines, studies published between 2010 and 2024 were searched in PubMed, Scopus, and the Cochrane Library. Three studies met the inclusion criteria, with most showing a significant reduction in patient anxiety when VR was used. Various VR applications, from immersive environments to educational modules, were assessed, with the Visual Analog Scale (VAS) being the most common anxiety measurement. VR shows promise as an anxiety-reducing tool in odontectomy. However, further randomized controlled trials are necessary to evaluate long-term effects and identify the most effective VR content and delivery methods.